In situ characterization of foreign object damage (FOD) in environmental‐barrier‐coated silicon carbide (SiC) ceramic. Issue 8 (6th May 2020) - Kedir, Nesredin; Garcia, Eugenio; Kirk, Cody; Guo, Zherui; Gao, Jinling; Zhai, Xuedong; Sun, Tao; Fezzaa, Kamel; Sampath, Sanjay; Chen, Weinong W.
Abstract: Environmental barrier coatings (EBCs) protect advanced ceramics and ceramic matrix composites (CMCs) from oxidation and corrosion in gas turbine engine environments. Foreign object damage (FOD), where debris impact the protective coatings, is a critical hazard which limits the turbine durability. Despite previous efforts to understand FOD in EBCs, a detailed understanding of the fundamental transient damage mechanisms is still lacking. In the current work, the real‐time FOD behavior of a mullite/ silicon EBC was visualized via a dynamic synchrotron X‐ray source in phase contrast imaging (PCI) configuration. Prior to the in situ FOD experiments, the microstructure and composition of the coating were, respectively, characterized using a scanning electron microscope (SEM) and X‐ray diffraction (XRD). The variation in the properties of the debris was modeled by 1.5mm diameter partially stabilized zirconia (PSZ) and silicon nitride (Si3 N4 ) spheres. A modified light‐gas gun setup, synchronized with the X‐ray beam, was used to propel the projectiles at velocities ranging between 300 and 355ms −1 . Coated samples were impacted under a fully backed support configuration and at normal incidence. Coating penetration and delamination, as well as projectile deformation at the bond coat resulted for FOD by PSZ spheres. Comparatively, projectile fracture, with subsequent rebound of fragments, as well as complete coating penetration and delamination at the substrate interface occurred for FOD by Si3 N4 spheres. Only cone cracking was observed for FOD by PSZ spheres, whereas back surface cracking was present for both projectile types. The driving forces for the observed damage mechanisms are qualitatively assessed.